KEDUDUKAN ANAK ANGKAT TERHADAP HARTA WARISAN ORANG TUA ANGKATNYA BERDASARKAN HUKUM ADAT KAMPAR DI DESA EMPAT BALAI KECAMATAN KUOK - Rinu Nabilla; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Based on Article 1 of Act Number 1 Concerning Marriage, it is startedthat Marriage is a spiritual bond between a man with a woman as husband andwife with the aim of forming a family (a happy and eternal household based onthe Almighty God). The presence of a child is a gift and a complement to thefamily. But, if a husband and wife do not have children, there is anotheralternative, namely the adoption of children. The purpose of writing this thesisis, first, to find out how the position of adopted children to the inheritance ofadoptive is based on Kampar Customary Law. Second, to find out the proses ofsettlement of disputes on inheritance of adoptive parents againts their adoptedchildren based on Kampar Customary Law.The type of research can be classified in the type of Sosiological Lawresearch that is research on the location or place studied. This research wasconduced in the Four Village, Kuok Sub-District, Kampar District, RiauProvince, which is a research to see the correlation between customary lawprevailing in the midst of society. From the results of this research there aretwo things that can be concluded. First, the position of adopted children incostumary law is the same as biological children. Secondly, in settlement ofdisputes that occur within the costum law’s community, assostance is requestedfrom the community or Ninik Mamak from each tribe to settle disputes or find asolution to the problem of the child.This the right inherit to adopted children against their adoptive parentsstill applient in the Kampar Costumary Law based on the Kampar Costumaryphilosophy, namely: the law in encoded Syara’, syara’ encoded in thekitabullah. The authors suggestion, first, the adopted child should respect hisadoptive parents like biological child of the family. Second, the role of NinikMamak i resolving child disputes must be more active in order to avoidongoing disputes.